Fracture mechanics of fiber reinforced concrete: Experimental study of composition, geometry and hybridization of fibers - Khaled Sanginabadi (Iranian Society of Structrual Engineering (ISSE), 2018)
Using of polymeric fibers for reinforced concrete structures has significantly developed in recent years. Polymeric fibers start their contribution in the behavior of concrete members after cracking. In order to a careful investigation into post-cracking behavior need to apply fracture mechanic concept (growth of cracks) in reinforced concrete members. For this purpose, in this research 14 concrete prisms (100×100×400 mm in dimensions) with 35 mm notch depth (at the center of tensile side) for four-point flexural strength test were fabricated. Fiber composition, geometry and hybridization percent were varied in these samples. Derived outputs illustrated that macro polypropylene (PP) fiber has no significant effect on concrete ductility, whereas it leads to increase the flexural strength. But micro polyester (PET) and PP fibers have more effective performance during forming cracks in concrete members. PET and PP fibers have a more suitable function during concrete cracking and the samples containing these fibers have no significant drop in their bearing while the cracking is started. In addition, samples reinforced with PP and PET fibers indicated that by increase in macro fibers, the flexural strength were increased where as ductility indices decreased. In general, samples reinforced with %60 of PP macro fibers and %40 PET micro fibers have the best performance.